Vehicle Safety System Integrated with GSM Network (Global System for Mobile Communications) on Vehicle Ignition System - Akhmad Riszal; Suryadiwansa Harun; Yanuar Burhanuddin; Abdul Hakim Md Yusop; Martinus; Arinal Hamni; Rizal Adi Saputra; Rizal Nazarrudin (Jurnal Inovasi Teknologi, 2025)
This research aims to design and create a sms-based motor vehicle security system with an ATMega 8535 microcontroller. This research utilizes hand phone technology and microcontroller. Making this tool has an economical price to secure motorized vehicles. Important prototypes in making this tool are the ATMega 8535 microcontroller, GSM Modem and HP. In making this tool the first thing to make is to make a microcontroller program for the controller. Making this program uses CV Avr soft ware (Code Vision Avr). After the program is finished, the program is downloaded to the microcontroller. Control is done by the microcontroller when it gets input. The result of this research is to get a vehicle security system that is integrated by the ignition system on a motorcycle. The process of securing a motorized vehicle when it is stolen is, the security system will send sms information that the motorcycle is stolen, the alarm sounds and the ignition system is cut off. To turn off the alarm and start the motorcycle, the owner sends an SMS with the format *ALOF# to the security system and starts the motorcycle normally (Pull the front brake three times then position the key to ON mode).